Regulating Damage from Sterile Inflammation: A Tale of Two Tolerances. Issue 4 (April 2017) - Wu, Shin-Rong; Reddy, Pavan
Abstract : The severity of immunopathology from non-infectious inflammation is mainly understood and is managed by targeting immune cells. However, the role of target tissues in determining damage severity has been largely overlooked. Here, we discuss the concept of 'tissue tolerance' for tissue-intrinsic programs that ameliorate organ damage in the setting of sterile immunopathology.